Development of a Virtual Model for Stainless Steel Forming - Bravo Vargas, Salvador (2017)
In this paper, a virtual model in ANSYS for the forming process of stainless steels whichallows obtaining the neutral fiber is presented. The neutral fiber, also known as K factor, allows determining the blank of a piece for its later forming. Due to the complexity of the forming processes in the industry, such as bending, shaping, and stamping, it is necessary to perform computational analyses. It is important to count on models that allow understanding the behaviorof the material during its processi ng to reduce subsequent manufacturing mistakes. In this paper,a finite element-based analysis method for the forming process of stainless steels is proposed, and also its comparison with physical experimentation is presented. A particular bending process was characterized and its comparison with physical tests of 201 and 304 stainless steels was undertaken. Such comparison shows a difference of 0.4 percent between them. The obtained K factor could be used directly for analytical calculations of the blank of parts or for the software development of sheet metal forming.